Understanding and Reporting of Environmental Costs in Financial Statements of The Rambak Industry Center Tulungagung - Meirini, Dianita; Rahayu, Tashya Novita Puji (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2024)
This research aims to identify environmental costs incurred by the Tulungagung rambak industry, as well as their understanding of reporting environmental costs in financial reports. Environmental costs are incurred to manage industrial waste, namely solid waste in the form of livestock hair and liquid waste in the form of cooking oil residue and lime water at the rambak industrial of Tulungagung. The concept of recognizing environmental costs and their accounting treatment uses the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK-EMKM) and the concept of green accounting. The research method used is a qualitative case study, The data was obtained from interviews with three informants who are owners of rambak home industries in Tulungagung. The interview results were identified regarding the understanding and implementation of environmental costs, both in terms of industrial waste management and their reporting in financial statements. The results of this research are that Tulungagung Rambak Industrial has implemented environmental costs for environmental prevention costs and environmental detection costs, such as halal cost, PIRT cost, freight cost, sack cost, and sapiteng cost. Conclusion the reporting of those environmental costs is still done by conventional accounting concepts and not yet by green accounting.